2013
DOI: 10.1016/j.brat.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Treating PTSD in refugees and asylum seekers within the general health care system. A randomized controlled multicenter study

Abstract: The study indicated that refugees and asylum seekers can be treated successfully for PTSD and depression in the general psychiatric health care system; NET appeared to be a promising treatment for both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 29 publications
(35 reference statements)
3
83
0
2
Order By: Relevance
“…However the studies differ in terms of relating factors (such as the mean age of the participants, the length of received treatment, the origin of the participants), which might have affected treatment outcome. In line with Haagen et al (2017) and Stenmark et al (2013), we did not find gender to influence treatment outcome. It can thus be concluded that potential factors influencing the therapy outcome are not yet sufficiently investigated and should be examined more systematically in further studies, including factors such as asylum status, housing, family reunification or personality factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However the studies differ in terms of relating factors (such as the mean age of the participants, the length of received treatment, the origin of the participants), which might have affected treatment outcome. In line with Haagen et al (2017) and Stenmark et al (2013), we did not find gender to influence treatment outcome. It can thus be concluded that potential factors influencing the therapy outcome are not yet sufficiently investigated and should be examined more systematically in further studies, including factors such as asylum status, housing, family reunification or personality factors.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of sociodemographic variables predicting treatment outcome, the results are mixed. Stenmark, Guzey, Elbert, and Holen (2014) found that female participants responded better to a treatment programme for PTSD than male participants, while other studies did not find gender to predict treatment outcome (Carlsson et al, 2005; Haagen et al, 2017; Stenmark, Catani, Neuner, Elbert, & Holen, 2013). In terms of age being associated with treatment outcome, a study with refugees from Bosnia-Herzegovina suggests that younger refugees might respond better to group treatment and/or medication in terms of PTSD symptom reduction than older ones (Drozdek, 1997), while Carlsson et al (2005) did not find associations between age and treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…European mental health care services generally offer psychotherapist or psychiatrist delivered, specialized mental health services that may involve a wide range of treatments, such as Cognitive Behavioural Therapy (CBT), Narrative Exposure Therapy (NET) (Stenmark, Catani, Neuner, Elbert, & Holen, 2013), Eye Movement Desensitization and Reprocessing (EMDR) (Ter Heide, Mooren, Kleijn, de Jongh, & Kleber, 2011), and individual-based multimodal interventions for PTSD (see Nickerson, Bryant, Silove, & Steel, 2011; Nose et al, 2017; Slobodin & de Jong, 2015; van Wyk & Schweitzer, 2014 for reviews) in refugees and asylum seekers. With respect to evidence for such interventions, a recent meta-analysis that examined psychological interventions for symptoms of PTSD in refugees and asylum seekers resettled in high-income countries identified 14 randomized controlled trials (RCTs) (Nose et al, 2017).…”
Section: Evidence-based Interventions For Refugeesmentioning
confidence: 99%
“…The United States, in particular, is the world's leading nation for refugee resettlement, with over 2.5 million refugees having been resettled since 1975 [1,2]. Studies have demonstrated that refugees tend to experience high levels of psychological distress [3,4,5,6], and, in turn, suffer from a disproportionately higher percentage of mental health problems [7,8]. Given the current global refugee crisis and ensuing sociopolitical, emotional, and psychological consequences, it is critical for public health scholars and practitioners to understand the needs of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Many refugees are exposed to significant rates of adverse and traumatic experiences, including persecution, exposure to war and violence, and losses of family members and friends [8,9,10,11]. As a result, refugees tend to suffer greater stress than non-refugee immigrants [12,13], and may experience posttraumatic stress, symptoms of depression, long term fatigue, and anxiety [14,15].…”
Section: Introductionmentioning
confidence: 99%